SOCIAL STATE AND ITS CHARACTERISTICS: (SOME THEORETICAL AND LEGAL ISSUES) - Akhmedshaeva Mavluda Akhatovna (Modern American Journals, 2025)
In this article is emphasized that, as a result of the constitutional reforms carried out in our country, the enshrinement of the legal foundations of the social state at the constitutional level has increased academic interest in issues related to the social state, its features, characteristics, and practical implementation. Consequently, scientific research in this field is not only theoretical but also, to a certain extent, practical in nature.
Keywords: State, constitution, law, legal state, social state, secular state, liberalism, social democracy, social policy, social protection.